Serological evaluation of respiratory syncytial (rs) and parainfluenza 3 (pi3) viruses in cattle from Cusco - Solís G., Galim (2010)
The objective of the present study was to determine the seroprevalence of respiratory syncytial (RS) and parainfluenza 3 (PI3) viruses in cattle from three communities of the province of Espinar, Cusco, Perú. Blood samples were collected from 406 cattle older than 6 months of age of both sexes for the detection of antibodies against the RC and PI3 viruses by viral neutralization test. The 85.0 and 87.4 of animals presented antibodies against the RS and PI3 viruses, respectively, where animals with 13-24 and >24 months old were the most affected age groups. Antibody titres against both viruses had a range of 2 to >256, where antibody titres of 16-64 against RS and PI3 viruses were detected in 61.4 and 58.3% of the animals. Antibodies against both viruses were detected in 76.4% of the animals. The results revealed that the RS and PI3 viruses are widely distributed in the cattle population of the three communities.